2020
DOI: 10.1186/s13046-020-01790-w
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Circular RNA hsa_circ_0001829 promotes gastric cancer progression through miR-155-5p/SMAD2 axis

Abstract: Background Accumulating evidences have shown that circular RNAs (circRNAs) play important roles in regulating the pathogenesis of cancer. However, the role of circRNAs in gastric cancer (GC) remains largely unclear. Methods In this study, we identified a novel upregulated circRNA, hsa_circ_0001829, in chemically induced malignant transformed human gastric epithelial cells using RNA-seq. Subsequent qRT-PCR and ISH assays were performed to detect the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Hsa_circ_0110389 is up-regulated in GC tissues and cells, and high hsa_circ_0110389 expression associates with advanced stages of GC and predicts poor prognosis RNA-seq analysis between malignant-transformed human gastric epithelial cells (GES-1-T cells) induced by MNNG and NC cells (GES-1-N cells) was conducted in our previous study [17,18], and the heat map expression results showed that hsa_circ_0110389, accession id according to the annotation of circBase (http://www.circbase.org/), was highly up-regulated in GES-1-T cells (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hsa_circ_0110389 is up-regulated in GC tissues and cells, and high hsa_circ_0110389 expression associates with advanced stages of GC and predicts poor prognosis RNA-seq analysis between malignant-transformed human gastric epithelial cells (GES-1-T cells) induced by MNNG and NC cells (GES-1-N cells) was conducted in our previous study [17,18], and the heat map expression results showed that hsa_circ_0110389, accession id according to the annotation of circBase (http://www.circbase.org/), was highly up-regulated in GES-1-T cells (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…CircRNAs play as ceRNAs to regulate target gene expression through miRNAs [29,30]. For example, circPGR was recently found to function as a ceRNA to promote estrogen receptorpositive breast cancer cell growth [31]; our recent study found that hsa_circ_0001829 functions as an oncogene in GC and exerts its effects via miR-155-5p/SMAD2 axis [18]. In current study, results of knockdown and overexpression assays revealed that hsa_circ_0110389 regulates GC cells proliferation, migration and invasion in vitro, and animal studies showed that hsa_circ_0110389 silencing inhibited tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…RNase R was purchased from Geneseed Biotech Co., Ltd. (Guangzhou, China). RNase R treatment was performed as described in a previous study [ 26 ]. In brief, total RNA (2 μg) was incubated with RNase R (3 U/μg) for 10 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%